Impact of Road Network Charging System on Pricing for General Cargo Transportation - Poliak, Miloš (Promet - Traffic&Transportation, 2012)
The paper defines the problem of pricing in general cargo by impact of toll in the first section. Different usage of a vehicle in individual transportation causes that it is not possible to calculate the toll uniformly for every cargo by constant price for the customer in the same transportation. The next part analyses the existing processes of the toll share for general transport described in Austria, Bohemia and Germany. None of the processes can be used for another state in general. The rest is a draft of the new method of toll share for general transport determination. Key words: transportation, pricing, cargo, toll, road